Method for preparing an adsorbent object
Through the combination with polymer binder and multi-stage drying treatment, the problem of high density and mechanical strength of adsorbent objects in the prior art is solved, and efficient production of adsorbent objects is achieved.
Patent Information
- Application Number
- CN202380051561.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-07-03
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to produce high-density, mechanically robust adsorbent objects on a large scale, especially metal-organic frame (MOF) and covalent-organic frame (COF) materials, and these materials are prone to damage under pressure, resulting in pore collapse and reduced fluid storage capacity.
By forming a wet frame substance, including an organic frame and the first solvent, and in contact with the polymer binder, partially drying, the solvent is removed to form a dried adsorbent object, followed by solvent washing and high temperature activation, forming an optimized adsorbent object.
It has achieved large-scale industrial production of high-density, mechanically robust adsorbent objects, maintained high volume efficiency and fluid storage capacity, and avoided pore collapse and adhesion problems.
Smart Images

Figure BDA0005225552580000151
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing an adsorbent object. The adsorbent object comprises one or more organic frameworks. The adsorbent object also comprises an organic polymer binder. Background Art
[0002] The present invention provides industrially relevant preparation of robust adsorbent objects comprising an organic framework. The organic framework is typically selected from metal-organic framework (MOF) and / or covalent-organic framework (COF) materials. For clarity, the term "framework" is used throughout as a general term to describe MOFs and COFs. MOFs and COFs are organic frameworks. The term "industrially relevant" refers to methods that can prepare several kilograms of adsorbent objects per day using cost-effective and readily available equipment. Therefore, laboratory preparation protocols and procedures for making gram quantities of samples using, for example, beakers and test tubes are generally not industrially relevant.
[0003] Organic frameworks, such as MOFs and COFs, are crystalline sorbent materials that can be used to adsorb and desorb gases. The terms "framework" and "organic framework" are used interchangeably to describe metal-organic frameworks (MOFs) and / or covalent-organic frameworks (COFs). These materials can offer many performance advantages over existing sorbent materials and are candidates for improved gas adsorption and storage systems, such as those required for practical transport systems. MOFs and COFs have attracted great interest, and many research teams and companies are actively developing synthetic routes and manufacturing methods. Examples of MOFs are HKUST-1, UiO-66, and ZIF-8.
[0004] The need to store as much gas as possible in a given volume of storage vessel means that the bulk density of the adsorbent material is very important. The higher the density, the more material can be packed into the available working volume. However, the density should not be at the expense of porosity and sorptive properties.
[0005] MOF and COF and many other adsorbent framework materials are usually synthesized in the form of thin low-density powders. Fine powders are not suitable for many uses of organic frameworks, such as large-scale storage or selective adsorption of components from fluids. The low bulk density of typical MOF or COF powders limits the amount of adsorbent materials that can be loaded into containers. In addition, the inevitable channeling and compaction of thin low-density powders cause the major problem of fluid flowing evenly through the powder bed. In order to make this adsorbent material useful in industry, it is necessary to form them into mechanically strong, larger objects with higher density, which maintain high volumetric efficiency. Conventional options for forming solid larger objects from fine powders include tableting and extrusion.
[0006] However, many organic frameworks are not strong under pressure. For example, the bonds in MOFs are based on metal coordination chemistry, so they are relatively weak. If many MOFs and COFs are subject to high compression forces, this may cause their internal pores to collapse. This collapse causes MOFs or COFs to become amorphous, thereby losing surface area and, in turn, fluid storage capacity. The high-pressure preparation process (e.g., tabletting) for forming compacted objects of MOFs and COFs can result in compacted objects having reduced surface area and poorer fluid storage capacity.
[0007] An alternative approach is to mix the framework powder with a plasticizer / liquid to form a paste / soft solid, then extrude the material to form an extrudate, followed by removal of the plasticizer / liquid to harden the extrudate. However, such extrudates often require the presence of a binder material (usually an inorganic particulate binder such as hydrated alumina) to obtain a mechanically strong object, and the use of pre-dried framework powders (particularly organic framework powders) may have some disadvantages, such as the introduction of unwanted mesopores and macropores porosity levels. Extrusion is a mechanically simple and widespread process and is an attractive preparation method.
[0008] In order for extrusion or any particle manufacturing process to be industrially relevant, it must be possible to produce processable extrudates / objects at industrially relevant rates using existing equipment. Most of the prior art published on extrusion (or other particle formation steps) of MOFs or COFs describes work that has been done on a small scale (e.g., in the laboratory). Typically a mixture or blend of a paste / soft solid containing an adsorbent powder plus a plasticizer / lubricant liquid is made into a single extrudate strand, dried, and then chopped. There is no description in the prior art of the physical properties required for a mixture to be extruded or otherwise formed into small objects to achieve large-scale industrially relevant processing. However, successful post-extrusion or general post-production processing of the small objects formed is critical to any larger scale production rates.
[0009] For the extrusion process, it is necessary to break or cut the extruded strands into smaller lengths ("extrudates"). This can be done by mechanical cutting or by relying on the breaking of longer extrudates during extrusion and subsequent processing. Extrudates are usually formed by mechanically cutting the extrudate strands using a die face cutter. The extrudates are cut by a rotating blade moving on the surface of the die-plate. This means that the extrudate can be cut into controlled lengths, which can be controlled by the rotation speed of the cutter tool and the design of the die.
[0010] In order for the extrudate cutting process or any cutting-based object forming process to work, the material should not adhere to any blade used to cut the material. If a large amount of material does adhere to the cutting tool, this will quickly lead to a buildup of material on the cutting tool, resulting in large clumps of material rather than discrete extrudates or objects. Objects (e.g., extrudates) also need to not adhere to each other or the sides of the equipment immediately after cutting or breaking. This is often a major problem with extrusion cutting processes because the extrudate is concentrated in a small space, resulting in frequent extrudate: extrudate impacts. If the extrudate or object is too soft and / or too sticky, they will stick to each other after impact. Also, if the extruded strands are too soft or too sticky, methods that rely on mechanical breaking of the extrudate strands (e.g., extrusion-spheronization) will not work.
[0011] The problem of not having the deformable material adhere to the cutting blades applies to other forms of material besides extrudates, such as flakes, slabs, tablets or other larger objects. Extrudates are a very convenient form, but it is also of industrial relevance to be able to cut or otherwise break other larger objects (e.g. larger "slabs" or large flat tablets formed by pan drying) into smaller objects using, for example, a tablet press or other cutting tool. The formation of smaller objects is generally followed by optional but highly preferred further processing steps, such as rounding in a spheronizer and / or controlled drying.
[0012] Thus, it can be seen that successful large-scale preparation of adsorbent framework objects by extrusion or other particle formation processes requires that the mixture being processed has specific physical properties. Any mixture cannot be too soft when cut or broken, otherwise it will stick to itself or to the sides of the equipment or cutting tools, quickly rendering the process unfeasible. If the mixture is too hard, the high pressures required to extrude the mixture or otherwise form the object may damage the porosity of the MOF or COF or generally make the particles too hard to be easily spheronized.
[0013] The use of a binder is generally important for providing sufficient robustness to an organic framework (or other) object. The binders described in the prior art often comprise inorganic particles, such as hydrated alumina. Such inorganic particulate binders need to be used at relatively high levels (e.g., 30 wt%) to be effective, and rely on particle: particle interlocking to provide robustness. Since the binder replaces the framework material, high levels of such binders essentially dilute the volumetric performance of such adsorbent objects. However, such particulate binders do not clog the pores of the framework material. Most of the prior art describes methods in which a preformed and dried MOF powder (typically a spray-dried powder) is mixed with a binder (typically an inorganic binder) and a plasticizer / lubricant and then extruded. The MOF powder may be spray dried and optionally ground prior to mixing with the binder and plasticizer and extruding. Other known methods spray dry a mixture of MOF powder and an inorganic binder and then extrude the spray-dried microparticles to simplify processing.
[0014] For clarity, the term "framework object" describes an object (eg, an extrudate) in which a majority (ie, >50 wt%) of the object comprises one or more framework materials, and mixtures and blends thereof.
[0015] The inventors have found that when the MOF or COF crystallites that form the framework object remain dispersed and generally have a small size before forming the object, an optimized organic framework object is formed. For example, it is better if the organic framework crystallites from the reaction mixture do not undergo a thorough drying step to form discrete, dried, solid particles before forming a larger object. On the contrary, it is better if the crystallites formed in the reaction mixture remain solvated (such as still having some free solvent) and dispersed before forming a larger object. Generally, smaller organic framework crystallites allow for more dense packing in the adsorbent object. However, a limited amount of pre-dried framework powder can be combined with a solvated framework (as described above) without excessive loss of beneficial properties. If sufficient solvent and stirring are provided, the aggregates of the previously dried framework powder can also be resolvated and re-dispersed. The method of the present invention allows the use of high levels of solvent in any resolvation process.
[0016] For the sake of clarity, in the context of the present application, "undried" describes a concentrated substance of framework material that has enough solvent to be deformable under moderate pressure (e.g., manual, pressure), but if formed into a shaped object, is solid enough to mostly maintain its shape when handled. Typically, the undried framework material will have less than 75% free solvent, or less than 70% free solvent, or less than 60% free solvent, or even less than 50% free solvent. "Wet" refers to a substance of framework material and solvent, which typically has enough free solvent, such as more than 60% or more than 70% or more than 80% solvent, to form a thick paste or slurry. "Dry" refers to an object or substance of a framework material that has been fully dried to form a hard, solid object. This type of physically hard framework object may still contain significant levels of solvent, which may be due to the high adsorption of typical framework materials (e.g., MOFs or COFs). Dry framework objects typically still contain up to 50% solvent.
[0017] Typically, "free" solvent refers to the portion of one or more solvents that can be removed from a material by drying at 25°C for 10 hours. Free solvent is loosely bound to the material and can affect the rheology of the object. Free solvent is a portion of total solvent. When measuring free solvent levels, sample sizes between 2g and 10g are typically used.
[0018] Thus, the wet material can be partially dried to first form an undried material, which is then further dried to form a dry material. For any given frame-containing mixture, the wet material will have a higher free solvent level than the undried material, which in turn will have a higher free solvent level than the dried material. However, the absolute amount of solvent in these different stages (wet, undried, dry) can be different for different frames and adhesives. The dry frame object can be subjected to further processing steps, such as solvent washing and activation at elevated temperatures, to completely remove residual solvent.
[0019] Without wishing to be bound by theory, it is believed that any drying step (e.g., spray drying) that forms the framework crystallites into a powder comprising discrete particles or microparticles inherently produces significant levels of macro- and meso-porosity in these larger dried aggregated particles. It is believed that the rapid removal of solvent involved in many drying methods produces larger pores or non-uniform hard areas. Even when a size reduction step is performed, these framework powders introduce unwanted levels of meso- and macro-porosity into any framework object formed from them, thereby reducing the volumetric performance of the object. High pressure can be used in the extrusion step to partially "drive out" at least a portion of this unwanted porosity, but this can easily collapse the internal pores of many organic frameworks. However, adsorbent framework objects can be prepared that incorporate a portion (i.e., <50%) of the framework material as a pre-dried powder in order to limit the amount of unwanted porosity.
[0020] The inventors have found that when a wet framework material (such as described above) is combined with a polymer binder (preferably in solution), partially dried to form an undried framework / binder material with specific properties, formed into a framework / binder object, and then further dried under controlled (limited temperature) conditions to form a dried framework adsorbent object, an optimized framework object is formed. Preferably, the dried extrudate or object is then subjected to additional solvent exchange and washing steps. The binder can be in solution (preferably an aqueous solution) to improve dispersibility, or can be in solid form, or can be a combination of solid and solution. Adding a binder in solid form (preferably as a fine powder) and mixing intensively can be advantageous because this does not introduce additional free solvent. Suitable binders may include soluble organic polymer materials, such as methyl cellulose or polyvinyl alcohol.
[0021] Controlling the physical properties of the undried framework / binder material, for example by controlling the level of free solvent in the undried framework / binder material, enables successful use of industrially relevant methods such as extrusion / spheronization. A preferred feature of the method is that a majority of the framework crystallites are not formed into discrete dried powder particles prior to being formed into a larger framework object. This avoids the introduction of unwanted mesopore and macropore porosity levels into the resulting framework object.
[0022] A problem is that the dispersed mixture of small framework crystallites formed in the diluted reaction mixture needs to be concentrated. Preferably, the crystallites have an average particle size of less than about 900nm or less than about 800nm or less than about 600nm or less than about 400nm or even less than about 200nm. The small size of the preferred crystallites makes the separation process (such as filtering) more difficult, and the step of appropriately aggregating the crystallites in the reaction mixture before separation may be advantageous. The solvent can always be removed by evaporation, but if at least some of the solvents present can be removed by other separation processes (such as filtering, sedimentation or centrifugation), it is preferred because this will also remove dissolved materials, such as unreacted raw materials in the removed solvent. The diluted reaction mixture (usually up to 5% or up to 10% solids) is concentrated to form a wet framework material that is generally greater than 10% solids. Generally, the wet framework material will contain <30% solid content. Then it needs to be contacted with a polymer binder (preferably in a solution) to obtain a wet adhesive material. Then the wet adhesive material is formed into an undried adhesive material by reducing the amount of the solvent. The wet binder material is generally too liquid "as is" to form discrete objects (particularly when the polymer binder is in solution). The solids level may be less than 20%. Removal of free solvent makes the binder material more solid-like. The undried binder material is now suitable for forming extrudates or other objects, followed by optional rounding and / or other process steps.
[0023] Typically, free solvent is a portion of one or more solvents that is not strongly bound to another substance (e.g., an adhesive polymer) and can be used to plasticize an adhesive, generally as a lubricant. Free solvent can be removed by drying for 10 hours at an ambient condition of 25°C. Solvent that does not evaporate under these conditions is not considered to be "free". The total level of solvent in a sample is determined by measuring the weight loss of a sample heated to 100°C for >10 hours under vacuum. The % solid content of a material is 100% minus the total solvent level. Preferably, the free solvent to be removed comprises water. When the free solvent comprises water, the level of the free solvent is typically characterized by water activity. All this needs to be done in an industrially relevant manner. Summary of the invention
[0024] The present invention provides a method for preparing an adsorbent object, wherein the method comprises the following steps:
[0025] (a) forming a wet framework material, wherein the wet framework material comprises:
[0026] (i) organic framework; and
[0027] (ii) a first solvent,
[0028] Preferably, the organic framework comprises a metal-organic framework (MOF), a covalent-organic framework (COF) or a mixture thereof;
[0029] (b) contacting the wet framework material with a polymeric binder to form a wet binder material;
[0030] (c) partially drying the wet binder mass to form an undried binder mass;
[0031] (d) extruding and / or cutting the undried binder material to form undried adsorbent objects;
[0032] (e) removing at least some of the first solvent from the undried sorbent object to form a dried sorbent object;
[0033] (f) contacting the dried adsorbent object with a second solvent to form a washed adsorbent object;
[0034] (g) removing at least some of the second solvent from the washed adsorbent object to form an unactivated adsorbent object;
[0035] (h) activating the unactivated adsorbent object by subjecting the unactivated adsorbent object to a temperature greater than 100° C. to form an adsorbent object.
[0036] Typically, the undried adhesive material is formed into an undried adsorbent object, such as an extrudate of a predetermined length. They are then preferably subjected to a further rounding step. The undried adsorbent object is then dried to form a dried adsorbent object. Preferably, step (e) is carried out under controlled and limited conditions (e.g. < about 80°C or less than about 60°C or less than about 40°C) or even under ambient conditions (e.g. about 20°C) to slowly dry the undried adsorbent object. It is believed that slowly drying the undried adsorbent object is important for avoiding cracking and fragmentation of the undried adsorbent object when the solvated adhesive material is dried and shrunk. Higher drying temperatures can be used for low volatility solvents (e.g. DMF), while lower drying temperatures are used for more volatile solvents (e.g. water or ethanol or methanol). The dried adsorbent object is then typically subjected to a washing step with a second solvent to remove unreacted material and excess adhesive to increase surface area, thereby obtaining a washed adsorbent object. Following any solvent washing step, the washed adsorbent body is then dried and activated at elevated temperature to form the adsorbent body. DETAILED DESCRIPTION
[0037] Throughout the specification, one or more aspects of the present invention may be combined with one or more features described in the specification to define different embodiments of the present invention.
[0038] Unless the context implies otherwise, references herein to the singular of a noun encompass the plural of the noun and vice versa. For example, the term adsorbent object is to be understood as also referring to a plurality of adsorbent objects, the term metal-organic framework (MOF) is to be understood as also referring to a plurality of metal-organic frameworks (MOFs), and the term covalent organic framework (COF) is to be understood as also referring to a plurality of covalent organic frameworks (COFs).
[0039] Throughout the specification, the words "comprise / comprises / comprising" will be understood to imply the inclusion of stated elements, integers or steps or groups of elements, integers or steps but not the exclusion of any other elements, integers or steps or groups of elements, integers or steps. The term "comprising" includes within its scope the terms "consisting of" or "consisting essentially of".
[0040] The term "consisting of" or variations thereof will be understood to imply the inclusion of a stated element, integer or step or group of elements, integers or steps and the exclusion of any other element, integer or step or group of elements, integers or steps.
[0041] The term "consisting essentially of" or variations thereof will be understood to imply inclusion of the recited elements, integers or steps or groups of elements, integers or steps, and that additional components may be present, but only those that do not materially affect the basic characteristics of the preparation, composition or compound.
[0042] As used herein, when qualifying a number or value, the term "about" is used to refer to a value that is within ±5% of the specified value.
[0043] A method for preparing an adsorbent object. The method comprises the following steps:
[0044] (a) forming a wet framework material, wherein the wet framework material comprises:
[0045] (i) organic framework; and
[0046] (ii) a first solvent,
[0047] Preferably, the organic framework comprises a metal-organic framework (MOF), a covalent-organic framework (COF) or a mixture thereof;
[0048] (b) contacting the wet framework material with a polymeric binder to form a wet binder material;
[0049] (c) partially drying the wet binder mass to form an undried binder mass;
[0050] (d) extruding and / or cutting the undried binder material to form undried adsorbent objects;
[0051] (e) removing at least some of the first solvent from the undried adsorbent object to form a dried adsorbent object;
[0052] (f) contacting the dried adsorbent object with a second solvent to form a washed adsorbent object;
[0053] (g) removing at least some of the second solvent from the washed adsorbent body to form an unactivated adsorbent body; and
[0054] (h) activating the unactivated adsorbent object by subjecting the unactivated adsorbent object to a temperature greater than 100° C. to form an adsorbent object.
[0055] Typically, it is necessary to first wash and concentrate the framework crystallites from a diluted reaction mixture typically used to synthesize such materials to form a wet framework material. Removal of bulk liquid can be accomplished in a variety of ways. This can be accomplished by spray drying, but as previously described, this can result in the formation of undesirably larger dried particles and can also leave undesirable residual material. Washing of the wet framework material can mean the presence of a mixture of solvents in the wet framework material.
[0056] Concentration of framework crystallites from a reaction mixture or wash mixture is commonly performed in the laboratory by the use of a centrifuge. Centrifuging a reaction mixture is very effective in separating solid particles from the surrounding liquid and can result in a more concentrated slurry or solid layer. Centrifugation can be continuous or batchwise and combined with other washing and separation methods. A preferred industrial solution is to concentrate the framework crystallites in the reaction mixture into a wet framework material by a filtration step. This can be done simply but does result in the filtered wet framework material having substantially higher levels of residual free solvent than, for example, high speed centrifugation.
[0057] Adding polymer binder solution further increases the level of solvent. This wet binder material is too liquid-like to be successfully extruded and / or cut. It is necessary to dry or free solvent reduction steps to form an undried binder material that is solid-like enough to be feasible for any extrusion and / or cutting steps.
[0058] As used herein, the term "free solvent" refers to a solvent that can be used to plasticize an adhesive. A solvent that is tightly held in the pores of a framework (for example) or tightly bound to an adhesive molecule or other substance is not "free" because it is not readily available to plasticize an adhesive. The water held in a hydrate is not "free" and cannot act as a lubricant and affect the rheology of the mixture. When the solvent is water, the level of free solvent is related to the measured water activity. The water activity of a material at a given temperature is defined as the ratio of the air humidity balanced with the sample at that temperature to the air saturation humidity at that temperature. Due to the simplification of the resulting method and the ease of industrial application, it is highly preferred if the first solvent contains water as much as possible.
[0059] Typically, the level of free solvent can be reduced by controlled evaporation or by adding moderate levels (e.g., up to about 40 wt%) of one or more porous fine powders that can adsorb at least some of the free solvent. Such powders can include silica, activated carbon, fine pre-dried organic frameworks, zeolites, or combinations thereof. For example, silica is able to strongly adsorb much of the solvent within its pores so that the solvent is no longer free. The level of free solvent in an object can be measured by measuring the weight loss of a sample at 25°C over a 10-hour period, as this temperature will only remove solvent that is not tightly bound or held by another substance.
[0060] The present invention provides a method for preparing a high-performance adsorbent framework object by extrusion and / or cutting method using a multi-stage drying method, wherein a wet framework material is contacted with a polymer binder, preferably in a solution, and even more preferably in an aqueous solution, to form a wet adhesive material. Preferably, using a high level of solvent means that the adhesive is well dispersed around the framework crystallites, and the multi-stage drying method means that the adhesive level in the final framework object does not need to be limited by intermediate processing requirements. Typically, the wet adhesive material then has enough free solvent to be removed to form an undried adhesive material that is more like a solid, and the undried adhesive material can be formed into an undried adsorbent object, which is then subjected to at least one further solvent reduction step. The undried adsorbent object can be formed by extrusion and / or cutting method. Preferably, before the further solvent reduction step, the undried adsorbent object is subjected to a rounding step to form a dried adsorbent object. The dried adsorbent object can undergo a washing step using a second solvent, and then dried to form a washed adsorbent object.
[0061] It is highly preferred if most or all of the framework crystallites are not subjected to a thorough drying step to form discrete dried particles before being formed into larger objects with a binder. A preferred method is to first synthesize the framework in a diluted reaction mixture and wash and / or concentrate to form a wet framework material. The concentration step can be accomplished by any known means and can include an aggregation step whereby small individual framework crystallites are aggregated together by chemical or mechanical (e.g., ultrasonic) means to form larger secondary aggregates that are more easily removed from the reaction mixture, such as by filtration or centrifugation, to form a wet framework material. Such in-situ aggregates are generally not strong enough to maintain any unwanted porosity, etc. during further processing.
[0062] The framework material that wets is then contacted with polymer binder, preferably in solution, to form wet binder material.Before slurry is contacted with organic polymer binder, it may be favourable to further remove some free solvents from wet framework material.Then reduce the level of free solvent in the wet binder material, have the rheological characteristic that is suitable for extruding and / or cutting until the undried binder material of gained, and can not dirty cutting tool, excessive deformation or adhere to the surface.Then undried binder material is cut to form less object and preferably through rounding.Then less undried adsorbent object is carried out gentle (slowly) drying step to form dried adsorbent object, usually followed by solvent washing step in second solvent.
[0063] Step (a) forms a wet framework material. Step (a) forms a wet framework material.
[0064] Preferably, step (a) is implemented by:
[0065] (i) contacting together:
[0066] (a) Framework precursor materials, such as metal-organic framework precursor materials and / or covalent organic framework precursor materials
[0067] materials; and
[0068] (b) a reaction solvent,
[0069] Thereby forming a diluted reaction mixture, wherein the diluted reaction mixture comprises:
[0070] (a) metal-organic framework crystallites and / or covalent organic framework crystallites; and
[0071] (b) a reaction solvent; and
[0072] (ii) concentrating the diluted reaction mixture by removing at least some of the reaction solvent and any other solvent to form a wet framework material, wherein the wet framework material may also contain the first solvent from any washing steps used to remove the reaction solvent and other undesirable materials. The first solvent used in any washing step may be the same as or different from the reaction solvent.
[0073] In step (i), contacting the framework precursor material and the reaction solvent together can be carried out by at least one of the following:
[0074] a) dissolving the framework precursor material in a solvent, typically water or an alcohol (eg ethanol); and / or
[0075] b) condensing the dissolved framework precursor materials to form framework crystallites, such as metal-organic framework crystallites and / or covalent organic framework crystallites.
[0076] Suitable conditions for the contacting step (i) (eg, solvent, reaction temperature, reaction time) vary depending on the precursor material and the framework crystallite, and such conditions will be within the scope of the skilled artisan.
[0077] Preferably, the metal-organic framework precursor material may be one or more metal ions, such as metal cations, and one or more organic ligands, such as multidentate organic ligands.
[0078] The one or more or more metal ions may be selected from the group consisting of ions of zirconium, iron, zinc, hafnium, magnesium or potassium. The metal ions may be provided by a salt of the metal ion (eg ZrCl4).
[0079] Multidentate organic ligand is an organic ligand that can provide two pairs or more pairs of electrons to form two or more coordination bonds in complex reaction. One or more or more organic ligands can comprise two or more oxygen and / or nitrogen atoms, which are suitable for providing a pair of electrons to form two or more coordination bonds. Preferably, the oxygen atom can exist as a carboxylate radical or a nitro group. Preferably, the nitrogen atom can exist as an amido group. Usually, a plurality of organic ligands can be aromatic carboxylates, aromatic amines and / or aromatic nitro. Preferably, the organic ligand can be selected from the group consisting of tetrakis(4-carboxyphenyl)porphyrin (TCPP), 1,4-phthalic acid (BDC), 1,3,5-benzenetricarboxylic acid (H3BTC), 1,3,5,8-(p-benzoyl)pyrene linker (H4TBAPy), 4',4"',4""',4"""'-(ethylene-1,1,2,2-tetrayl)tetrakis(([1,1'-biphenyl]-3-carboxylic acid))(H4ETTC).
[0080] Preferably, the covalent-organic framework precursor materials can be: boronic acids (such as phenyldiboronic acid), which can form borates (condensation with alcohols), boroxides (self-condensation) or borazines (condensation with amines); nitriles (such as 1,4-dicyanobenzene), which can form triazines; or amines and aldehydes (such as aniline and benzaldehyde), which can form imines.
[0081] Preferably, the framework crystallites in the diluted reaction mixture are aggregated into larger secondary particles before removing a portion of the reaction solvent.
[0082] Preferably, the aggregation step is performed by at least one of the following:
[0083] (a) adding an anti-solvent;
[0084] (b) adding polymeric aggregation aids, including polymers used as binders; and / or
[0085] (c) Application of high-frequency ultrasound.
[0086] Preferably, the antisolvent is miscible with the reaction solvent and has an HSP hydrogen bonding parameter that differs from that of the reaction solvent by more than about 10 MPa. 0.5 The hydrogen bond HSP parameter dH.
[0087] The term "anti-solvent" as used herein refers to a solvent in which the solute (i.e., dissolved substrate) (e.g., metal-organic framework microcrystals and / or covalent organic framework microcrystals) is less soluble or completely insoluble than the solvent in which the solute (e.g., metal-organic framework microcrystals and / or covalent organic framework microcrystals) is soluble. The anti-solvent should be miscible with the reaction solvent. Adding an anti-solvent to a solvent containing a solute causes the solute to separate or precipitate from the solvent, i.e., the anti-solvent reduces the solubility of the solute in the solvent, causing it to separate from the solvent as a solid precipitate or aggregate.
[0088] Preferably, the solvent removal step (ii) is carried out by at least one of:
[0089] (a) filtration step;
[0090] (b) a sedimentation step;
[0091] (c) a centrifugation step;
[0092] (d) an evaporation step; and
[0093] (e) any combination thereof.
[0094] Alternatively or additionally, step (a) may be performed by:
[0095] i. contacting a metal-organic framework precursor material and / or a covalent organic framework precursor material (the framework precursor material is as described herein) and an optional reaction solvent together;
[0096] ii. mixing and grinding a metal-organic framework precursor material and / or a covalent organic framework precursor material together to form a reaction mixture; wherein the reaction mixture comprises metal-organic framework crystallites and / or covalent organic framework crystallites;
[0097] iii. contacting the reaction mixture with a first solvent; and
[0098] iv. Removing some but not all of the first solvent to form a wet framework material.
[0099] The reaction solvent may be the same as the first solvent. Alternatively, the reaction solvent may be different from the first solvent.
[0100] Preferably, the mixing and grinding of the metal-organic framework precursor material and / or the covalent organic framework precursor material can be carried out in a grinder, such as a ball mill using, for example, steel balls, stone balls or ceramic balls as grinding media. The mixing and grinding steps are usually carried out with solid precursor materials, but can also be carried out in the presence of a grinding solvent, which can be removed before the reaction mixture is contacted with the first solvent. Such methods are suitable for batch and continuous operations and provide energy-efficient synthesis methods.
[0101] After step ii., the reaction mixture may be subjected to washing and / or purification steps to remove any impurities and / or unreacted precursor material.
[0102] Suitable milling and mixing conditions (eg, speed, intensity, temperature, additives, reaction time) vary depending on the precursor material and framework crystallites, and such conditions will be within the scope of the skilled artisan.
[0103] Preferably, the framework material is in particulate form during step (a). The framework material may be dispersed in a gel or slurry. More preferably, the framework material is in particulate form having an average particle size of less than 900 nm.
[0104] Preferably, the frame material is in the form of crystallites.
[0105] Preferably, the framework material has a small primary particle size, preferably having a weight average particle size of about 5 nm to about 900 nm, or about 10 nm to about 800 nm, or about 12 nm to about 700 nm, or about 15 nm to about 500 nm. Small primary particles generally increase the particle packing in the adsorbent object to obtain a higher object density. The method of measuring particle size is described in more detail below. The particle size of the framework material is preferably measured after the material has been formed into the adsorbent object. However, the particle size of the framework material can also be measured before step (a).
[0106] It is believed that particle size control of the framework material is important to ensure the formation of high quality, high density adsorbent objects. If the particles are too large, this may result in the formation of adsorbent objects with poorer (lower) density distribution and / or poorer robustness.
[0107] Step (a) can also be implemented by dispersing the pre-dried framework powder in the first solvent. Preferably, the framework powder is dispersed by a high shear step. Suitable equipment includes a high shear mixer (e.g., IKA Ultra Turrax T25) or an ultrasonicator (e.g., Bandelin SONOPULS HD 2000). The pre-dried framework powder can also be dispersed in the first solvent by a wet grinding step. Suitable equipment includes a ball mill or a roller mill. Typically, a high level of solvent (e.g., > about 70wt%) and a high level of stirring are required to ensure good redispersion of the framework powder and to avoid problems associated with pre-drying of the framework material.
[0108] Step (b) forms a wet adhesive mass. Step (b) contacts the wet framework mass with a polymeric binder to form a wet adhesive mass.
[0109] The polymer binder may be in solution, or it may be added as a solid (preferably as a fine powder) or as a slurry. Preferably, the polymer binder is added as a solution. The polymer binder is typically mixed with the wet frame and extensive mixing is performed to ensure homogeneity.
[0110] Step (c) forms an undried adhesive substance. Step (c) partially dries the wet adhesive substance to form an undried adhesive substance (which may also be referred to as a drier adhesive substance or a partially dried adhesive substance or an intermediate partially dried adhesive substance). In other words, step (c) removes (e.g., evaporates) and / or captures (e.g., adsorbs onto an adsorbent material) at least some but not all of the first solvent from the wet adhesive substance to form an undried adhesive substance.
[0111] Step (c) can be realized in several different ways.Wet adhesive material can be further dried before cutting.This can be completed in for example scraped film evaporator, then the undried adhesive material of gained is cut and formed into smaller object.Wet adhesive material can be allowed to dry on flat surface to form undried adhesive material, then cut in cutting grinder or tablet press or other suitable cutting equipment.This method is to remove (for example evaporation) at least some but not all of the first solvent to form the example of undried adhesive material from wet adhesive material.
[0112] Another option is to add additional adsorbent solid materials that can adsorb some of the free first solvent. This material can be selected from fine activated carbon or silica or zeolite or even some pre-dried framework materials (if the level is not too high) and mixtures thereof. The framework powder can be the same as the powder forming the framework material, or it can be different. Preferably, the additional adsorbent material is selected from activated carbon, zeolite, organic framework, silica and mixtures thereof. The additional adsorbent solid material can even be a polymer binder if sufficient amounts are added in fine powder form. If the amount of the additional adsorbent solid material added is limited, some limited additional porosity is acceptable. This method is an example of capturing at least some but not all of the first solvent from a wet binder material to form an undried binder material, i.e., some of the first solvent is bonded to, for example, an additional adsorbent material.
[0113] A preferred option is to form an undried binder mass from a wet binder mass by combining evaporation of free solvent from the wet binder mass with addition of a limited amount of additional adsorbent solid material. This can occur in different unit operations, for example, removing some of the free first solvent in a wiped film evaporator and then adding additional adsorbent solid material in a mixer or extruder.
[0114] Suitable silicas for use as additional adsorbent material are precipitated silicas or fumed silicas, preferably fumed silicas. Suitable fumed silicas include the Aerosil series from Evonik. Suitable precipitated silicas include the Sipernat series from Evonik.
[0115] Typically, the undried adhesive material formed by reducing the level of free solvent is dried for 10 seconds before any cutting step. -1 and >4.0x 10 at 25°C 5 The viscosity of the undried adhesive mass is in the range of 10s.mPa.s. The undried adhesive mass retains sufficient free solvent to be deformable under pressure and impact so that it can be rounded, for example, in a spheronizer. Typically, the viscosity of the undried adhesive mass is in the range of 10s.mPa.s. -1 and less than 1.25 x 10 at 25°C6 mPa.s.
[0116] Step (d) forms an undried adsorbent object. Step (d) extrude and / or cut the undried adhesive material to form an undried adsorbent object. Preferably, step (d) extrude and / or cut the undried adhesive material to form an undried adsorbent object.
[0117] Step (e) forms a dried adsorbent object. Step (e) removes at least some of the first solvent from the undried adsorbent object to form a dried adsorbent object. Preferably, step (e) is performed gradually, for example at a temperature below about 80°C, or below about 50°C, or below about 40°C, or even at ambient temperature.
[0118] Step (f) forms a washed adsorbent object. Step (f) contacts the dried adsorbent object with a second solvent to form a washed adsorbent object.
[0119] Step (g) forms an unactivated adsorbent object. Step (g) removes at least some of the second solvent from the washed adsorbent object to form an unactivated adsorbent object.
[0120] Step (h) Activation Step. Step (h) activates the unactivated adsorbent object by subjecting the unactivated adsorbent object to a temperature greater than 100° C. to form an adsorbent object.
[0121] Optionally, step (g) and step (h) may occur simultaneously.
[0122] Wet framework material. A wet framework material is formed in step (a). The wet framework material comprises: (i) an organic framework; and (ii) a first solvent. Preferably, the framework comprises an organic framework selected from a metal-organic framework (MOF) and / or a covalent organic framework (COF). Most preferably, the wet framework material comprises a metal-organic framework. Preferably, the wet framework material is a wet organic framework material.
[0123] It may be preferred that, after initial formation, the wet framework material is subjected to one or more washing and reconcentrating steps.The first solvent may be the same as the reaction solvent, or the first solvent may be different depending on the washing step.
[0124] Framework. The framework is an organic framework. Most preferably, the framework is a metal-organic framework.
[0125] Organic framework. Preferably, the organic framework comprises a metal-organic framework (MOF), a covalent-organic framework (COF) or a mixture thereof. Preferably, the organic framework is a metal-organic framework (MOF), a covalent-organic framework (COF) or a mixture thereof. The organic framework may comprise a mixture of more than one metal-organic framework (MOF) and / or more than one covalent organic framework (COF) or a combination thereof.
[0126] Preferably, the organic framework material is one or more metal-organic frameworks (MOFs) selected from the following:
[0127] (i) Zr-containing MOFs;
[0128] (ii) Zn-containing MOFs, such as zeolitic imidazolate frameworks and Zn-containing UTSA-16 and CALF-20;
[0129] (iii) MOF-74 and its derivatives;
[0130] (iv) Al-based MOFs;
[0131] (v) Fe-based MOFs;
[0132] (vi)M(F 6-x )L x family MOF;
[0133] (vii) Cu-based MOFs;
[0134] (viii) Co-based MOFs, including Co-UTSA-16;
[0135] (ix) Cr-based MOFs;
[0136] (x) Nb-based MOFs;
[0137] (xi) Ni-based MOF;
[0138] (xii) Mn-based MOF;
[0139] (xiii) mixed metal MOFs; and
[0140] (xiv) any combination thereof.
[0141] Suitable Zr-containing MOFs include UiO-66, UiO-67, UiO-68, NU-1000, PCN-222, MOF-808, and Zr-fumaric acid and its chemically functionalized derivatives.
[0142] Suitable ZIF monoliths include ZIF-7, ZIF-8, ZIF-67, ZIF-71 and ZIF-90.
[0143] Suitable MOF-74 derivatives include Mn, Ni, Co, Cu and Zn variants.
[0144] Suitable Al-based MOFs include Al-fumaric acid, MIL-53, CAU-10, MIL-160(Al), and Al-soc-MOF-1.
[0145] Suitable Cr-based MOFs include MIL-100(Cr) and MIL-101(Cr).
[0146] Suitable M(F 6-x )L x The family of MOFs includes SIFSIX-3-Ni, TIFSIX-3-Ni, NbOFFIVE-1-Ni and SIFSIX-2-Cu-i.
[0147] Suitable Cu-based MOFs include HKUST-1 and ROS-17.
[0148] Suitable Co-based MOFs include cobalt-based UTSA-16 and its derivatives.
[0149] Suitable Fe-based MOFs include MIL-100(Fe) and MIL-101(Fe).
[0150] Suitable mixed-metal MOFs include MOFs based on mixtures of two or more metals selected from Fe, Ti and Zn.
[0151] Suitable MOFs can include mixed-ligand or co-crystallized MOFs, in which the MOF includes at least two chemically different organic ligands bonded to the same metal ion. This feature can help tune the chemical behavior of the MOF.
[0152] Preferably, the two chemically different organic ligands are chemical analogs. Chemical analogs refer to the structural aspects of the ligands, especially the skeleton and the parts involved in bonding with the metal ion are the same.
[0153] A particularly preferred feature is chemical analogs for chemically different organic ligands, such that the organic ligands have the same framework structure but differ from each other due to functionalization of the framework structure. The structural similarity of how different organic ligand anions bond to metal ions means that variants of a particular MOF can be formed. If the organic ligands are too dissimilar, the MOF may be amorphous or full of defects.
[0154] For example, many MOFs have dicarboxylic acids as their organic ligands. Each carboxylic acid group participates in bonding with a metal ion. The backbone structure refers to the structure between two carboxylic acid binding groups.
[0155] The size of the framework determines the size of the pores formed by the organic ligands attached to the metal ions. The chemical differences come from the functional pendant groups attached to the framework.
[0156] Illustrative examples are shown below. In these cases, the backbone structure is (deprotonated) terephthalic acid (A).
[0157]
[0158] Additional illustrative examples are discussed below. Two exemplary chemical analogs are terephthalic acid (CAS 100-21-0) and 2-aminoterephthalic acid (CAS 10312-55-7). Other exemplary analogs of terephthalic acid include 2-bromoterephthalic acid (CAS 586-35-6), 2-nitroterephthalic acid (CAS 610-29-7), trimellitic acid (CAS 528-44-9), and 2-hydroxyterephthalic acid (CAS 636-94-2).
[0159] The use of such chemical analogs allows the manufacture of specific MOFs with variable chemical properties. It may also be preferred that the two chemically different organic ligands comprise different framework structures. The use of organic ligands with different framework structures may allow the introduction of "defects" in the monolithic object where the structure of the MOF is incomplete, or allow for more complex MOF structures. In some cases, these defects increase porosity.
[0160] Preferably, the molar ratio of the first organic ligand to the second organic ligand is greater than about 1: 2. More preferably, the molar ratio of the first organic ligand to the second organic ligand is greater than about 1: 3. Such ratios are effective to improve the physical characteristics and / or chemical properties of objects made from such co-crystals.
[0161] Sorbent objects comprising a mixture of framework materials can be prepared by mixing the different framework materials together before adding the polymeric binder.
[0162] Suitable MOF adsorbent objects may include a mixture of MOF crystallites made with different ligands. For example, a suitable UiO-66-based MOF may include a mixture of UiO-66-BDC and UiO-66BDC-NH2.
[0163] Suitable COFs for use in the present invention include imine and / or hydrazone linked COFs. Thus, the adsorbent object may include imine and / or hydrazone linked COFs.
[0164] Examples of imine-linked COFs include 3D-COOH-COF, 3D-COOH-COF, 3D-CuPor-COF, 3D-CuPor-COF-0P, 3D-OH-COF, 3D-Por-COF, 3D-Por-COF-0P, 3D-Py-COF, 3D-Py-COF-2P, 4PE-1P, 4PE-1P-oxi, 4PE-2P, 4PE-3P, 4PE-TT, BF-COF-1, BF-COF-2, BW-COF-AA, BW-COF-AB, CCOF-1, CCOF-2, CC-TAPH-COF, COF-112, COF-300, COF-320, COF-366-Co, COF-366-F4-Co, COF-366-F-Co, COF-366, COF-366-(Ome)2-Co, COF-505, COF-AA-H, COFBTA-PDA, COF-DL229, COF-LZU1, COF-SDU1, COF-TpAzo, CuP-Ph COF, CuP-TFPh COF, DAAQ-TFPCOF, DABQ-TFP-COF, DAQ-TFPCOF, DaTP, DhaTab, 2,3-DhaTab, 2,5-DhaTab, 2,3-DhaTph, 2,5-DhaTph, 2,3-DhaTta, 2,3-DmaTph、DMTA-TPB1 / 2'、DMTA-TPB1 / 3'、DMTA-TPB1 / 4'、DMTA-TPB1 / 5'、DMTA-TPB2、DMTA-TPB3、DMTA-TPB4、EB-COF:Br、EB-COF:Cl、EB-COF:F、EB-COF:I、FL-COF-1、HAT-COF、HAT-NTBA-COF、HBC-COF、HB-COF-AA、HB-COF-AB、HCC-H2P-COF、HO2C-H2P-COF、SIOC-COF-5、SIOC-COF-6、SIOC-COF-7、TAPB-BMTTPA-COF、TAPB-PDACOF、TAPB-TFP、TAPB-TFPB、Tb-DANT-COF、TBI-COF、TDFP-1、TEMPO-COF、TFB-COF、TfBD、TfpBDH、TH-COF-1、Thio-COF、TPA-COF-1、TPA-COF-2、TpBD、TpBD-2NO2、TP-BDDA-COF、TpBDH、TPBD-ME2、TPB-DMTP-COF、TpBD-NH2、TpBD-NHCOCH3、TpBD-NO2、TpBD-(OMe)2、TpBPy、TP-COF-BZ、TP-COF-DAB、Tp-DANT-COF、TPE-COF-I、TPE-COF-II、TPE-COF-III、TPE-COF-IV、TP-EDDA-COF、TpMA、TpPa-1、TpPa-2、TpPa-F4、TpPa-NO2、TpPa-Py、TpPa-SO3H、TpPa-SO3H-Py、Tp-Stb、TPT-COF-1、TPT-COF-2、TpTD、TpTG-Br、TpTG-Cl、TpTG-I、TpPa-1-F2、Tp-Ttba、TRIPTA、TTF-COF、TTF-Py-COF、TTI-COF、TzDa、Tp-Azo、HPB-COF、ILCOF-1-AA、ILCOF-1-AB、iPrTAPB-TFP、iPrTAPB-TFPB、LZU-301、LZU-301-sol、LZU-70、LZU-72、LZU-76、N3-COF、NN-TAPH-COF、NS-COF、NUS-10、NUS-14、NUS-15、NUS-9、HO-H2P-COF、OH-TAPH-COF、PC-COF、PI-2-COF、PI-3-COF、Por-COF、Py-1P COF、Py-1PF COF、Py-2,2'-BPyPh-COF, Py-2,3-BPyPh-COF, Py-2,3-DHPh-COF, Py-2PE COF, Py-3PEBTD COF, Py-3PE COF, Py-An COF, Py-DHPh COF, PyTTA-BFBIm-iCOF, RT-COF-1, SA-COF, Salen-COF, SB-PORPy, SIOC-COF-3-AB and SIOC-COF-4-AB. ,
[0165] Examples of hydrazone-linked COFs include COF-42-bnn, COF-42-gra, COF-43-bnn, COF-43-gra, COF-ASB, COF-LZU8, CPF-1, CPF-2, and TFPT-COF.
[0166] Preferably, the COF may be any one of those listed herein or any combination thereof.
[0167] The first solvent and the reaction solvent. The first solvent describes the solvent or solvent mixture present in the wet framework material. In addition to the solvent added for washing or other purposes, the first solvent may contain a residual amount of solvent from the early stage of the method. Typically, the first solvent is different from the solvent (reaction solvent) used in the synthesis of the framework. Alternatively, the first solvent may be the same as the reaction solvent. The reaction solvent is usually difficult to handle, and it is preferred if it can be washed out and replaced with the first solvent to simplify subsequent processing. Preferred first solvents include dimethyl sulfoxide (DMSO), polar aprotic solvents (such as dimethylformamide (DMF), dimethylacetamide (DMS) and N-methyl-2-pyrrolidone), low molecular weight alcohols (including ethanol and methanol), water, acetone, organic acids (such as acetic acid) and mixtures and combinations thereof. Particularly preferred is water.
[0168] Polymer binder. Preferably, the polymer binder is an organic polymer binder selected from the group consisting of polyvinyl alcohol (PVA), polyvinyl acetate, polyvinyl alcohol / acetate copolymers, polyimides, polyamides, polyvinyl pyrrolidone, polyacrylates including polyacrylic acid, polycarboxylates, polyethylene glycol, poly(1,4-phenylene-ether-ether-sulfone) (PFEES), poly(tetrahydrofuran) (PTHF), polylactic acid and its derivatives, or biopolymer-based materials such as polysaccharide gums including xanthan gum, guar gum, alginate, chitosan, cellulose-based polymers such as cellulose, cellulose acetate, hydroxypropyl methylcellulose (HPMC), methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose phthalate (HPMCP), or any mixtures and combinations thereof. Preferred binder mixtures include PVA and cellulose-based polymers, particularly hydroxyethylcellulose or methylcellulose.
[0169] Wet adhesive material. A wet adhesive material is formed in step (b). It may be preferred that the wet adhesive material is formed from a dried framework material that has been appropriately dispersed in a first solvent. Typically, the wet adhesive material will contain less than about 30% by weight solids content, or less than about 25% solids content, or less than about 20% solids content.
[0170] Undried binder material. An undried binder material is formed in step (c). It may be preferred that the undried binder material contains less than about 75% free solvent, or less than about 70% free solvent, or less than about 60% free solvent, or even less than about 50% free solvent. For any given adsorbent framework, the undried binder material contains less free solvent than the wet binder material.
[0171] Generally, it is important to control the rheology of the undried binder material. The rheology of the undried binder material is a complex combination of factors, such as the framework particle size, the amount of the first solvent present, the nature of the organic polymer binder and the presence of other materials. Generally, the mixture being cut must be sufficiently "solid-like" if it is to be successfully cut without messing.
[0172] In addition, a preferred option is to subject the formed object to a rounding step after cutting or breaking - for example in a spheronizer. The rounding of the formed object is preferably used as a dust reduction step. However, in order to round the extrudates, they need to be sufficiently deformable to achieve this. In general, there is an optimal operating range for the rheological values of the mixture being cut. When water is used as solvent, this means that there is an optimal water activity range.
[0173] One measure of how "solid-like" a material is is its viscosity. It is therefore generally important that the viscosity of the undried adhesive mass is within certain limits.
[0174] Therefore, the undried adhesive material in the preferred method of the present invention is usually dried within 10 seconds. -1 When the 5 mPa.s or greater than about 4.0 x 10 5 mPa.s or greater than about 5.0 x 10 5 mPa.s or greater than about 6.0 x 10 5 mPa.s or greater than about 7.0 x 10 5 mPa.s or even greater than about 1.0 mPa.s x 10 6 The viscosity of the undried adhesive material is generally 10 s. mPa.s. The preferred viscosity can be selected based on the nature and design of the cutting and subsequent processing steps. -1 When the 6 mPa.s or less than about 2.0 x 10 6 mPa.s or less than about 1.25 x 10 6 Viscosity in mPa.s.
[0175] Undried sorbent object. An undried sorbent object is formed in step (d).
[0176] Dried sorbent object. A dried sorbent object is formed in step (e).
[0177] Second solvent. Preferred second solvents include water and low molecular weight alcohols, including ethanol and methanol. The second solvent may include a mixture of solvents. More than one second solvent may be used in the washing step. Typically, the second solvent is different from the first solvent or the reaction solvent or the solvent used to form any polymer binder solution.
[0178] Washed Adsorbent Body. A washed adsorbent body is formed in step (f).
[0179] Unactivated sorbent object. An unactivated sorbent object is formed in step (g).
[0180] Adsorbent Object. The adsorbent object comprises a frame material and a polymer binder. Typically, the adsorbent object has a minimum internal dimension of less than about 10 mm. This can be measured by optical means (e.g., microscopy). Typically, the adsorbent object has a viscosity greater than about 0.7 g / cm 3 The encapsulation density.
[0181] Hansen Solubility Parameters. HSP values for most solvents can be found in standard reference tables, such as the CRC Handbook of Solubility Parameters and Other Cohesion Parameters (2nd Edition).
[0182] Method for measuring viscosity. A suitable device for measuring the viscosity of undried adhesive materials is the Anton Paar MCR 92 Rheometer, which has a 25 mm diameter plate, a 25 degree cone with a gap of 3.0 mm, and is measured at 25°C. Approximately 2 g of sample is placed on the plate, the upper cone is lowered to the target gap distance, excess sample is removed from the sides and the rotational viscosity is measured. Typically, the viscosity is measured at up to 50 s -1 Viscosity is measured over a range of shear rates. For the purpose of this document, the viscosity of a material is measured at 10 s -1 The viscosity measured at .
[0183] Methods for measuring water activity. The water activity of a material is defined as the fraction of the relative humidity of the atmosphere in equilibrium with the material, i.e., the ratio of the partial pressure of water vapor above the material to that above pure water at the same temperature. The term "relative humidity" (or RH) is used to describe water in the atmosphere or gas phase in equilibrium with a solid and is expressed as a percentage, where 100% is the relative humidity of pure water in a closed system. Thus, for any material, the water activity value (aw) is defined as %RH / 100.
[0184] Suitable equipment includes the HC2-AW probe connected to a Hygrolab C1 display unit, both from Rotronic Measurement Solutions. The equipment should be properly set up and operated in accordance with the manufacturer's instructions. The RH of the material is measured by placing a sample of the material within the measurement chamber of the HC2-AW such that >1 / 4 of the available volume is filled with sample, sealing the chamber and allowing the measurement to reach equilibrium as indicated on the display.
[0185] Unless otherwise stated, water activity measurements were performed at 25°C.
[0186] Method for characterizing the particle size distribution of particles in an adsorbent object by SAXS. The particle size distribution of adsorbent particles forming an adsorbent object can be characterized by SAXS. In principle, in a SAXS experiment, light is scattered due to the contrast in electron density between two phases. On this basis, the size of equivalent spherical particles or other shapes can be calculated. The SAXS intensity at a specific angle depends on the electron density contrast. This also depends on the size of the particles. Large particles scatter at small angles, small particles scatter at larger angles. To generate the measurement results, a piece of adsorbent material is placed on a sample holder. For SAXS, X-rays are generated by synchrotron radiation. One or more sets of data are collected to cover the entire range of scattering angles. Kratky instruments can be used to collect small-angle scattering at larger scattering angles (1e-1 to 4e-0 degrees). Bonse Hart instruments can be used to collect small-angle scattering at smaller scattering angles (2.2e-3 to 5e-1 degrees). In this case, the two data sets are combined into a single scan after background subtraction, and the data are subsequently de-smeared. These decontaminated data are then converted into a volume size distribution function through regularization techniques. The volume distribution function is the final output of the process.
[0187] Measurement of the size of the framework crystallites. The size distribution of the framework crystallites in the reaction mixture can be measured by dynamic light scattering. Suitable equipment includes the NANO-flex II from Colloid Metrix operated according to the manufacturer's instructions. The sample probe can be inserted directly into the reaction mixture. Dilution of the reaction mixture is usually not required.
[0188] Embodiments of the present invention. The following are embodiments of the present invention.
[0189] 1. A method for preparing an adsorbent object, wherein the method comprises the following steps:
[0190] (a) forming a wet framework material, wherein the wet framework material comprises:
[0191] (i) organic framework; and
[0192] (ii) between 50 wt % and 95 wt % of a first solvent,
[0193] Preferably, the organic framework comprises a metal-organic framework (MOF), a covalent-organic framework (COF)
[0194] or a mixture thereof;
[0195] (b) contacting the wet framework material with a polymeric binder to form a wet binder material;
[0196] (c) partially drying, preferably removing at least some but not all of the first solvent from the wet adhesive mass to form an undried adhesive mass;
[0197] (d) extruding and / or cutting the undried binder material to form undried adsorbent objects;
[0198] (e) removing at least some of the first solvent from the undried sorbent object to form a dried sorbent object;
[0199] (f) contacting the dried adsorbent object with a second solvent to form a washed adsorbent object;
[0200] (g) removing at least some of the second solvent from the washed adsorbent body to form an unactivated adsorbent body; and
[0201] (h) activating the unactivated adsorbent object by subjecting the unactivated adsorbent object to a temperature greater than 100° C. to form an adsorbent object.
[0202] 2. The method according to embodiment 1, wherein step (a) is implemented by:
[0203] (i) contacting together:
[0204] (a) a metal-organic framework precursor material and / or a covalent organic framework precursor material; and
[0205] (b) a reaction solvent,
[0206] Thereby forming a diluted reaction mixture, wherein the diluted reaction mixture comprises:
[0207] (a) metal-organic framework crystallites and / or covalent organic framework crystallites; and
[0208] (b) a reaction solvent,
[0209] (ii) removing the reaction solvent from the diluted reaction mixture;
[0210] (iii) contacting the concentrated reaction mixture with a first solvent; and
[0211] (iv) removing some but not all of the first solvent to form a wet framework material.
[0212] 3. The method according to embodiment 2, wherein the metal-organic framework crystallites and / or covalent organic framework crystallites in the diluted reaction mixture are aggregated into larger secondary particles before removing a portion of the first solvent.
[0213] 4. The method according to embodiment 3, wherein the aggregation step is performed by at least one of the following:
[0214] (a) adding an anti-solvent;
[0215] (b) adding polymeric aggregation aids, including polymers used as binders; and / or
[0216] (c) Application of high-frequency ultrasound.
[0217] 5. The claim according to embodiment 4, wherein the antisolvent is miscible with the reaction solvent and has an HSP hydrogen bonding parameter that differs from that of the reaction solvent by more than about 10 MPa. 0.5 The hydrogen bond HSP parameter dH.
[0218] 6. The method according to any one of embodiments 2-5, wherein the solvent removal step (ii) is carried out by at least one of the following:
[0219] (a) filtration step;
[0220] (b) a sedimentation step;
[0221] (c) a centrifugation step;
[0222] (d) an evaporation step; and
[0223] (e) any combination thereof.
[0224] 7. The method according to any one of the preceding embodiments, wherein the wet framework material is subjected to a roller milling treatment.
[0225] 8. The method according to embodiment 1, wherein step (a) is performed by:
[0226] i. contacting a metal-organic framework precursor material and / or a covalent organic framework precursor material (the precursor material is as described herein) and an optional reaction solvent together;
[0227] ii. mixing and grinding a metal-organic framework precursor material and / or a covalent organic framework precursor material together to form a reaction mixture; wherein the reaction mixture comprises metal-organic framework crystallites and / or covalent organic framework crystallites;
[0228] iii. contacting the reaction mixture with a first solvent; and
[0229] iv. Removing some but not all of the first solvent to form a wet framework material.
[0230] 9. The method according to any one of the preceding embodiments, wherein the organic polymer binder is selected from the group consisting of polyvinyl alcohol (PVA), polyethylene imine, polyimide (PI), polyvinyl pyrrolidone, polyvinyl formal, polyacrylic acid, sodium polyacrylate, polyethylene glycol, polypropylene glycol, poly(1,4-phenylene-ether-ether-sulfone) (PFEES), poly(dimethylsiloxane) (PDMS), poly(tetrahydrofuran) (PTHF), polyolefins, polyamides, chitosan, cellulose, including cellulose acetate, hydroxypropyl methylcellulose (HPMC), methylcellulose, carboxymethyl cellulose, hydroxypropyl methylcellulose phthalate (HPMCP), and any combination thereof.
[0231] 10. The method according to any one of the preceding embodiments, wherein the metal-organic framework (MOF) is selected from:
[0232] (i) Zr-containing MOFs;
[0233] (ii) MOFs containing Zn;
[0234] (iii) MOF-74 and its derivatives;
[0235] (iv) Al-based MOFs;
[0236] (v) Fe-based MOFs;
[0237] (vi)M(F 6-x )L x family MOF;
[0238] (vii) Cu-based MOFs;
[0239] (viii) Co-based MOFs;
[0240] (ix) Cr-based MOFs;
[0241] (x) Nb-based MOFs;
[0242] (xi) Ni-based MOF;
[0243] (xii) Mn-based MOF;
[0244] (xiii) mixed metal MOFs; and
[0245] (xiv) any combination thereof.
[0246] 11. The method according to any one of the preceding embodiments, wherein step (c) is performed by at least one of the following:
[0247] (i) evaporation of the solvent; and / or
[0248] (ii) adding an adsorbent powder to the wet binder material, wherein the adsorbent powder is selected from silica, zeolite, activated carbon, graphene, a metal-organic framework, a covalent organic framework, or a combination thereof.
[0249] 12. The method according to any one of the preceding embodiments, wherein the undried adhesive material formed in step (c) is dried within 10 s. -1 and 3.0x 10 at 25°C 5 mPa.s to 3.0x 10 6 Viscosity between mPa.s.
[0250] 13. The method according to any one of the preceding embodiments, wherein the first solvent is water and the undried adhesive material has a water activity of 0.5 to 0.9, or 0.55 to 0.85, or even 0.6 to 0.8.
[0251] 14. The method according to any one of the preceding embodiments, wherein the adsorbent object comprises:
[0252] (i) more than 50 wt% of a metal-organic framework material and / or a covalent organic framework material; and
[0253] (ii) Less than 20 wt% of a polymeric binder.
[0254] 15. The method according to any one of the preceding embodiments, wherein the metal-organic framework is selected from NbOFFIVE-1-Ni, and the polymeric organic binder is selected from polyvinyl alcohol or methylcellulose.
[0255] 16. The method according to any one of the preceding embodiments, wherein the undried sorbent objects are subjected to spheronization.
[0256] Each of the references mentioned herein is hereby incorporated by reference in its entirety, as if each reference were set forth in its entirety herein.
[0257] Although specific examples and / or embodiments of the present invention have been illustrated and described, it will be apparent to those skilled in the art that various other changes and modifications may be made without departing from the spirit and scope of the present invention. Therefore, it is intended that all such changes and modifications within the scope of the present invention are covered in the appended claims.
[0258] Example
[0259] A 1 liter reaction mixture was prepared, which included MOF (UiO-66-NH2) crystallites having an average particle size of less than 900 nm dispersed in a reaction solvent comprising water and 10% solid content.
[0260] The sample was divided into four equal aliquots and each aliquot was centrifuged at 5250 g for 15 min in a Jeol JR15.
[0261] The supernatant was decanted from each sample flask, leaving a wet solid layer at the bottom of the flask. 250 g of methanol was then added to each flask and the samples were stirred to redisperse and wash the microcrystals.
[0262] The flask was then centrifuged again at 5250 g for 40 minutes to form a thick solid layer (wet framework material) containing MOF, methanol and any residual reactants / solvent from the reaction mixture. The solid layer was analyzed to have a solids content of 27.5%.
[0263] 280 g of the wet frame was then mixed with 280 g of a 2.6 wt% aqueous solution of methylcellulose to form a wet adhesive mass. It had a solids level of 14.9% and was -1 and 2.54x 10 at 25°C 4 mPa.s viscosity and 0.95 water activity.
[0264] The level of the first solvent (in this case a mixture of water and methanol) was reduced by stirring the wet adhesive mass in a Kenwood kitchen stand mixer, impinging the stirred mixture with hot air from a hair dryer. This was continued for 50 minutes to give an undried adhesive mass having a solids content of 27.9%. This material was a very thick but still viscous paste.
[0265] 0.5 g of Sipernat 22S silica was mixed into 150 g of the above undried binder material. This resulted in an even more solid-like material. The solids content of the material was 29.8% with a viscosity of 10 s. -1 and 5.8x10 at 25°C 5 mPa.s viscosity and 0.81 water activity.
[0266] The undried adhesive material was then extruded through a manual spaghetti maker. The extrudates could be easily extruded without adhering to each other and could be easily cut. Samples of the extrudates were manually cut into 5 mm lengths and the cut extrudates were manually rounded to form approximately spherical beads (undried adsorbent objects).
[0267] The undried adsorbent object was then further dried at ambient conditions (21° C.) for 24 hours and formed hard, solid beads (dried adsorbent object) having a solids content of 77% and a water activity of 0.4.
[0268] 1.2 g of the beads were then placed in 100 ml of methanol (second solvent) for 48 hours. The methanol was then replaced and the adsorbent object was left for another 48 hours. The washed beads (washed adsorbent object) were removed from the methanol and allowed to dry under ambient conditions. The washed and dried beads (unactivated adsorbent object) were then activated by heating to 105° C. in a vacuum oven for 12 hours to obtain the final adsorbent object. The activated beads had a 1050 m 2 / g of BET area.
Claims
1. A method for preparing an adsorbent object, wherein the method comprises the following steps: (a) forming a wet framework material, wherein the wet framework material comprises: (i) organic framework; and (ii) between 50 wt % and 95 wt % of a first solvent; (b) contacting the wet framework material with a polymeric binder to form a wet binder material; (c) partially drying the wet binder mass to form an undried binder mass; (d) extruding and / or cutting the undried binder material to form undried adsorbent objects; (e) removing at least some of the remaining first solvent from the undried sorbent object to form a dried sorbent object; (f) contacting the dried adsorbent object with a second solvent to form a washed adsorbent object; (g) removing at least some of the second solvent from the washed adsorbent body to form an unactivated adsorbent body; and (h) activating the unactivated adsorbent object by subjecting the unactivated adsorbent object to a temperature greater than 100° C. to form an adsorbent object.
2. The method according to claim 1, wherein step (a) is implemented by: (i) contacting together: (a) a metal-organic framework precursor material and / or a covalent organic framework precursor material; and (b) a reaction solvent, Thereby forming a diluted reaction mixture, wherein the diluted reaction mixture comprises: (a) metal-organic framework crystallites and / or covalent organic framework crystallites; and (b) a reaction solvent, (ii) removing the reaction solvent from the diluted reaction mixture; (iii) contacting the concentrated reaction mixture with a first solvent; and (iv) removing some but not all of the first solvent to form a wet framework material.
3. The method of claim 2, wherein the metal-organic framework crystallites and / or covalent organic framework crystallites in the diluted reaction mixture are aggregated into larger secondary particles before removing the reaction solvent.
4. The method according to claim 3, wherein the aggregation step is performed by at least one of: (a) adding an anti-solvent; (b) adding polymeric aggregation aids, including polymers used as binders; and / or (c) Application of high-frequency ultrasound.
5. The claim of claim 4, wherein the antisolvent is miscible with the reaction solvent and has an HSP hydrogen bonding parameter that differs from that of the first solvent by more than 10 MPa. 0.5 The hydrogen bond HSP parameter dH.
6. The method according to any one of claims 2 to 5, wherein one or both of steps (ii) and (iv) are implemented by at least one of the following: (a) filtration step; (b) a sedimentation step; (c) a centrifugation step; (d) an evaporation step; and (e) any combination thereof.
7. The method of claim 1, wherein the wet framework substance is formed by dispersing a pre-dried framework material in a first solvent.
8. The method of claim 1, wherein step (a) is performed by: i. contacting a metal-organic framework precursor material and / or a covalent organic framework precursor material and an optional reaction solvent together; ii. mixing and grinding the metal-organic framework precursor material and / or the covalent organic framework precursor material together to form a reaction mixture; wherein the reaction mixture comprises metal-organic framework crystallites and / or covalent organic framework crystallites; iii. contacting the reaction mixture with a first solvent; and iv. Removing some but not all of the first solvent to form a wet framework material.
9. The method according to any of the preceding claims, wherein the polymer binder is an organic polymer binder selected from the group consisting of polyvinyl alcohol (PVA), polyvinyl acetate, polyvinyl alcohol / acetate copolymers, polyimides, polyamides, polyvinyl pyrrolidones, polyacrylates including polyacrylic acid, polycarboxylates, polyethylene glycol, poly(1,4-phenylene-ether-ether-sulfone) (PFEES), poly(tetrahydrofuran) (PTHF), polylactic acid and its derivatives, or biopolymer-based materials such as polysaccharide gums including xanthan gum, guar gum, alginates, chitosans, cellulose-based polymers such as cellulose, cellulose acetate, hydroxypropyl methylcellulose (HPMC), methylcellulose, ethylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose phthalate (HPMCP), or any mixtures and combinations thereof.
10. The method according to any one of the preceding claims, wherein the metal-organic framework (MOF) is selected from: (i) Zr-containing MOFs; (ii) Zn-containing MOFs; (iii) MOF-74 and its derivatives; (iv) Al-based MOFs; (v) Fe-based MOFs; (vi)M(F 6-x )L x family MOF; (vii) Cu-based MOFs; (viii) Co-based MOFs; (ix) Cr-based MOFs; (x) Nb-based MOFs; (xi) Ni-based MOF; (xii) Mn-based MOF; (xiii) mixed metal MOFs; and (xiv) any combination thereof.
11. The method according to any one of the preceding claims, wherein step (c) is performed by at least one of: (i) evaporation of the solvent; and / or (ii) adding an additional adsorbent solid material to the wet binder mass, wherein the additional adsorbent solid material is selected from silica, zeolite, activated carbon, graphene, metal-organic framework, covalent organic framework or a combination thereof.
12. A method according to any one of the preceding claims, wherein the undried adhesive material formed in step (c) is dried within 10 s. -1 and 3.0x 10 at 25°C 5 mPa.s to 3.0x 10 6 Viscosity between mPa.s.
13. A method according to any one of the preceding claims, wherein the first solvent comprises water and the undried binder material has a water activity of between 0.5 and 0.
9.
14. The method of any preceding claim, wherein the sorbent object comprises: (i) more than 50 wt% of metal-organic framework materials and / or covalent organic framework materials; and (ii) Less than 20 wt% of a polymeric binder.
15. The method according to any one of the preceding claims, wherein the framework material is a metal-organic framework selected from NbOFFIVE-1-Ni and the polymeric organic binder is selected from polyvinyl alcohol or methylcellulose.
16. The method according to any one of the preceding claims, wherein the undried sorbent bodies are subjected to a spheronization treatment.